2000
DOI: 10.1038/labinvest.3780006
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of ECV304 as a Human Endothelial Cell Model Defined by Genetic Analysis and Functional Responses: A Comparison with the Human Bladder Cancer Derived Epithelial Cell Line T24/83

Abstract: SUMMARY:Early reports indicated that ECV304 was a spontaneously-transformed line derived from a Japanese human umbilical vein endothelial cells (HUVEC) culture. Many morphological, immunochemical, and genetic studies provided further evidence that ECV304 was a valuable biomedical research tool and could be used to study processes that include angiogenesis in vitro and signal transduction by a variety of G protein-coupled receptors. However, several distinct differences between ECV304 and HUVEC are now apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 22 publications
1
105
0
Order By: Relevance
“…Moreover, in both studies the authors employed ECV304 cells, a cell line that has been considered as being of endothelial origin. However, recent studies convincingly demonstrated that they are derived from epithelial cells of bladder cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in both studies the authors employed ECV304 cells, a cell line that has been considered as being of endothelial origin. However, recent studies convincingly demonstrated that they are derived from epithelial cells of bladder cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports revealed genetic similarities between ECV304 and T24, a human bladder epithelial cancer cell line, by comparing their DNA fingerprints. 45,46 Nevertheless, ECV304 shows many endothelial characteristics, resembles Cl-2, a porcine brain microvascular endothelial cells and differs from T24 in phenotype. 47 ECV304 cells not only show endothelial morphology, but also express endothelial markers, uptake Ac-LDL and undergo tube formation in Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…ECV-304 was originally described as an immortalized endothelial cell line (32). However, more recent evidence has suggested that ECV-304 is a derivative of the human bladder carcinoma cell line T24 (33). For transfections and imaging, cells were grown on collagen coated glass bottom dishes (Matek).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%